Sustainability Of Small Medium Enterprises And Economic Growth: A Meta Analysis - Aqil Teguh Fathani; Novia Amirah Azmi; Annisa Weriframayeni (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study was conducted to determine the thematic trends of Small and Medium Enterprises (SMEs) and Economic Growth research, which focuses on policies, governance, communication patterns, and strategies. The research questions have been made more concrete by applying structure and bibliometric analysis to provide additional information that is not yet fully understood or analyzed; 1) What is the relationship between the topics of SMEs and economic growth, and how are they grouped? (2) What key themes have been used to promote SMEs and economic growth for the greater good of society? The research material of 224 documents is drawn from the Scopus database and covers the topics "Small and Medium Enterprises," "Economic Growth," and "2019-June 2022.". A meta-analysis on the sustainability of SMEs and Economic Growth yields 12 clusters and 149 prominent themes with close and intricate interactions. They are refined into a new, more current framework for SMEs' sustainability and economic success. Policies, behavior, financial systems, governance, and technology are currently the most important elements since they are interdependent in developing small and medium-sized firms (SMEs) to survive and compete optimally in the free market.